Web-Based Tourism Information System as Information Media in Kepahiang District - Agung Dimas Kusuma; Sri Handayani; Surya Ade Saputera (Jurnal Komputer, Informasi dan Teknologi, 2022)
Advances in information and communication technology today provide many conveniences for human activities in all fields. The management of data to become information that was previously complicated and took a long time to complete, becomes fast and light when done using technological facilities. As a result, human needs for technology are getting higher because it can help the effectiveness and efficiency of a job. Kepahiang is a place that stores a thousand natural beauties and diversity, such as waterfalls, hills, beautiful natural scenery and interesting and unique photo spots. On the basis of the identification of the problems that have been described above, the formulation of the problem in this study is how to make web-based tourism information system as an information medium in Kepahiang Regency. The Web-Based Tourism Information System as an Information Media in Kepahiang Regency was built using the Hypertext Prepocessor (PHP) programming language. This information system was built to facilitate the Kepahiang Regency Tourism Office in the process of conveying information and also as a place or forum for the promotion of tourism promotion places in Kepahiang Regency, so that it is more efficient and on target. .